Prática reflexiva na formação inicial de professores : intervenções no PIBID/Química por meio da autoscopia - Takahashi, Danieli Azanha Gazzoni (2018)
This paper presents the results of a qualitative research whose objective was to understand the potentialities that emerge from the use of autoscopy, in an educational context, for the formation of the reflexive practice of undergraduate students in Chemistry, who participated in a program of initiation to teaching. In the studied context, three-phase autoscopy was used during the application of Didactic Sequences on Chemical and Hydrocarbon Bonds for 1st grade students. and 3rd. year of the Secondary Education that are part of the subproject of Chemistry / PIBID-UEM. In order to answer the research question "What are the potential of autoscopy for the reflections of pibidians, in teaching situations, in the school context in Chemistry classes?", A methodological path was sought that includes the following steps: application of a questionnaire at the beginning and end of activities, replanning and application of didactic sequences. Data analysis was performed based on Bardin (2014) and obtained through different instruments and video recording. The results of this research reveal that autoscopy, in the context investigated, presents elements of reflection on action and reflection for action. Thus, although it is a complex process, it was possible to identify the positive effects of autoscopy at several moments, such as: in the registers, in the discussions, in the collaborative and individual moments of teacher training, especially on reflective practice